The Role of Concerned Countries in the Effectiveness of Unilateral Sanctions (Relying on the Unilateral Sanctions of the United States of America Against Iran) - Ahdieh Zangi Ahrami; Ahad Bagherzadeh; Hamid Azizi Moradpour (پژوهشهای حقوقی)
Although unilateral sanctions usually evoke the special role of the sanctioner countries as the main cause of human rights adverse effects caused by the imposition of sanctions, but this issue should not lead to ignoring the role and responsibility of the target countries in the extent of the effects and providing the human rights needs of their residents. In other words, unilateral sanctions (primary and secondary) inevitably always contain side effects, the amount of which can always depend on various factors. So far, most of the books and articles written in the field of sanctions have examined sanctions and human rights violations from the point of view of the sanctioning country, and limited research sources have also examined sanctions from the perspective of the target countries and third countries. One of the most important goals of internal sanctions is to review the internal structures and laws and subsequently modify the structures and laws that intensify the sanctions, and in this article, it is referred to as self-sanctions. Third countries can also support their nationals who are engaged in trade with the sanctioned country by imposing blocking regulations while preventing the violation of their sovereignty by the sanctioned countries. In this article, an attempt has been made to explain the role and responsibility of the concerned countries in sanctions (sanctioner, target and third party), and examine the structures, laws and regulations of the target country (especially Iran) and its role in the effects of sanctions. At the end, we will provide solutions to modify and change them.